Diamondoids as tracers of late gas charge in oil reservoirs: Example from the Tazhong area, Tarim Basin, China. (1st October 2019) - Zhu, Guangyou; Zhang, Zhiyao; Milkov, Alexei V.; Zhou, Xiaoxiao; Yang, Haijun; Han, Jianfa
Abstract: Significant petroleum resources occur in the Ordovician carbonate reservoirs of the Tazhong area (Tarim Basin, China) in accumulations of black oil, volatile oil and condensate. However, the factors controlling the distribution of pools with different fluid phases remain poorly understood. Here, we integrate geological and conventional oil/gas geochemical data with an extensive dataset on diamondoids and propose a model for the occurrence of petroleum fluids in the area. Oils in the study area contain low variety and concentration of diamondoids and organic-sulfur compounds (OSCs) and have oil-dissolved wet gas mostly co-generated with oil. In contrast, liquids in the condensate reservoirs are significantly enriched in various types of diamondoids and OSCs, and have dry associated gas with methane enriched in 13 C and relatively high content of H2 S. We interpret that mature gas from deeper Cambrian strata, likely generated from thermally cracked oils and affected by thermochemical sulfate reduction (TSR), invaded the condensate reservoirs. Black oil reservoirs did not receive this late gas charge and this preserved their oil phase. The 1D burial history models and data on fluid inclusions suggest that oil charged all studied Ordovician reservoirs in the Late Permian – Triassic time, while the late gas charge occurred in selected reservoirs in the Late Himalayan time (∼10 Ma). Diamondoids proved to be useful indicators of the late gas charge as their variety and concentrations in liquids from the study area show good correlation with the extent of gas invasion.